Ngaji Tilam Tradition: A Living Hadith Study on the Strengthening of Social Cohesion in the Muncung Village Community, Tangerang - Abdul Aziz; Muhammad Alif (Sufiya Journal of Islamic Studies, 2025)
This research analyzes the Ngaji Tilam tradition in Kampung Muncung, Tangerang, through the living hadis approach to understand how the community embodies the values of hadith in cultural practices. Ngaji Tilam, which is the post-funeral recitation of the Qur'an dedicated to the deceased, is examined as a complex socio-religious phenomenon. Using a qualitative-descriptive method and data collection techniques through participatory observation and in-depth interviews with community leaders and practitioners, this study finds that the tradition functions as a multifunctional social mechanism. On one hand, it represents the actualization of hadith values regarding mutual assistance, charity, and honoring guests. On the other hand, it serves as a social adhesive that strengthens community cohesion, collective solidarity, and the emotional resilience of grieving families. Through the structural functional perspective, this ritual is viewed as a subsystem contributing to the overall stability and integration of society.